SpyGlass DS-guided lithotripsy for pancreatic duct stones in symptomatic treatment-refractory chronic calcifying pancreatitis - Gerges, Christian; Pullmann, David; Bahin, Farzan; Schneider, Markus; Siersema, Peter D.; Neuhaus, Horst; van Geenen, Erwin-Jan M.; Beyna, Torsten (Endoscopy International Open, 2019)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) and/or extracorporeal shock wave lithotripsy are first-line therapies for draining an obstructed pancreatic duct (PD) in painful chronic calcifying pancreatitis (CCP). Pancreaticoscopy has shown promising success rates in small series.Materials and methods This study was a retrospective analysis of a clinical database. Included were all digital single-operator digital video (SOV) pancreaticoscopy-guided interventions (n = 23) on CCP patients (n = 20) between 2015 and 2017. Success and complication rates were collected from the database. Clinical success was determined by assessing pain level score (NRS) and quality of life (QoL) using standardized questionnaires.Results Overall technical success rate (successful SOV-pancreaticoscopy and PD drainage) was 95 %. Adverse events occurred in 7 of 23 procedures (30 %) and included extravasation from the PD (n = 1), self-limiting post-sphincterotomy bleeding (n = 1) and post-ERCP pancreatitis (PEP) (n = 6). At 3- to 6-month follow-up, 95 % of patients reported improvement in symptoms and reduction in intake of analgesics. Mean NRS decreased from 5.4 (±1.6) to 2.8 (± 1.8) (P < 0.01). Clinical success was achieved in 95 % of patients.Conclusions Digital SOV-guided lithotripsy was found to be safe and effective in this highly selected population of CCP patients. PD decompression had a beneficial effect on pain reduction and QoL.